Jejuno-ileal bypass, enteric hyperoxaluria, and oxalate nephrosis: a role for polarised light in the renal biopsy. Issue 9 (September 1998) - Hicks, K; Evans, G B; Rogerson, M E; Bass, P
Abstract : Enteric hyperoxaluria, a complication of jejuno-ileal bypass, is associated with renal failure owing to oxalate nephrosis or tubulo-interstitial nephritis. A 54 year old woman developed renal failure 17 months after jejuno-ileal bypass for morbid obesity. Renal biopsy showed widespread acute on chronic damage to the tubulo-interstitial compartment with extensive deposition of oxalate crystals. The extent of oxalate deposition was only evident on polarisation of the biopsy.